Write it down, make it happen eaudiobook Knowing what you want and getting it!. - Klauser, Henriette Anne (Tantor Media, 2018)
A simple and effective guide to turning your dreams into reality by taking matters into your own hands, filled with down-to-earth tips and easy exercises. In Write It Down, Make It Happen , Henriette Anne Klauser, PhD, explains how simply writing down your goals in life is the first step toward achieving them. Writing can even help you understand what you want. In this book, you will hear stories about ordinary people who witnessed miracles large and small unfold in their lives after they performed the basic act of putting their dreams on paper. Klauser's down-to-earth tips and easy exercises are sure to get your creative juices flowing. Before you know it, you'll be writing your own ticket to success. With Write It Down, Make It Happen you can find the perfect mate, buy your dream house, get a great new job, wake up happier, travel the world, or even have a better relationship with your teenager.